Integrated biological wastewater treatment for meat and dairy industry - Hlushen, Alena; Chyrykava, Marharyta; Aliashkevich, Iryna; Hubchyk, Kiryl (Journal of the Belarusian State University. Ecology, 2023)
About 200 enterprises producing meat product and more than 50 enterprises of the dairy industry operate in the Republic of Belarus. Up to 70 % of the water used in these industries is contaminated with fatty substances. At present, physicochemical methods (coagulation and flocculation) and biological treatment using microorganisms-destructors of fats and oils are most widely used for the treatment of fat-containing wastewater, it is advisable to use these treatment methods in combination. Recently, more and more attention has been paid to the complete or partial replacement of chemical flocculants by biological or microorganisms with flocculating ability. In this paper, the process of wastewater treatment of meat and dairy industry enterprises was studied using a consortium of flocculant microorganisms and the microbial preparation Antoil. The investigated microbial consortium was shown to be as active as the most common polyacrylamide-based synthetic flocculants used for wastewater treatment. The flocculating activity was 92–98 %. It has been established that the process of purification of the studied wastewater with the help pf the consortium of microorganisms used depends on the temperature and pH value of the effluents. Dairy and meat industry wastewater was treated with an efficiency of 60.9–98.0 % in 7 days in the temperature range of 10–40 ⁰C and pH 4–9. It is shown that the use of a consortium of flocculant microorganisms makes it possible to achieve high rates of wastewater treatment of a cheese-making plant and a poultry farm not only in terms of suspended solids, but also in terms of COD. The effectiveness of the combined use of a consortium of flocculant microorganisms and the microbial preparation Antoil for the treatment of wastewater from poultry farms and maintaining the treatment efficiency at a high level (86.5–92.9 %) during burst discharges has been practically confirmed.